Beyond the limits of 1D coherent synchrotron radiation. (19th July 2018) - Brynes, A D; Smorenburg, P; Akkermans, I; Allaria, E; Badano, L; Brussaard, S; Danailov, M; Demidovich, A; De Ninno, G; Gauthier, D; Gaio, G; van der Geer, S B; et al.
Abstract: An understanding of collective effects is of fundamental importance for the design and optimisation of the performance of modern accelerators. In particular, the design of an accelerator with strict requirements on the beam quality, such as a free electron laser (FEL), is highly dependent on a correspondence between simulation, theory and experiments in order to correctly account for the effect of coherent synchrotron radiation (CSR), and other collective effects. A traditional approach in accelerator simulation codes is to utilise an analytic one-dimensional approximation to the CSR force. We present an extension of the 1D CSR theory in order to correctly account for the CSR force at the entrance and exit of a bending magnet. A limited range of applicability to this solution—in particular, in bunches with a large transverse spot size or offset from the nominal axis—is recognised. More recently developed codes calculate the CSR effect in dispersive regions directly from the Liénard–Wiechert potentials, albeit with approximations to improve the computational time. A new module of the General Particle Tracer code was developed for simulating the effects of CSR, and benchmarked against other codes. We experimentally demonstrate departure from the commonly used 1D CSR theory for more extreme bunch length compression scenarios at the FERMI FEL facility. Better agreement is found between experimental data and the codes which account for the transverse extent of the bunch, particularly in more extreme compression scenarios.